TASK-BASED LANGUAGE TEACHING (TBLT) IN THE MIDDLE SCHOOL CLASSROOM: FOCUSING ON HOW AUTHENTIC TASKS (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2025)
Task-Based Language Teaching (TBLT) is an instructional approach that centers language learning around the completion of meaningful tasks. This article explores the application of TBLT within the middle school context, with a specific emphasis on the pivotal role of authentic tasks. Middle school learners (typically ages 11-14) are in a critical transitional phase, making engagement and relevance crucial for effective language acquisition. Authentic tasks those that mirror real-world language use and possess an inherent communicative purpose offer a powerful mechanism for bridging the gap between classroom learning and practical application. This article delves into the principles of TBLT, provides practical strategies for designing and implementing genuinely authentic tasks (such as planning a local event, conducting a class survey, or creating an instructional video), and discusses the pedagogical benefits, including increased motivation, collaborative skills development, and enhanced communicative competence, while also addressing common implementation challenges in diverse middle school settings.